The Transformation of Indonesian on TikTok: A Pragmatic Study of Digital Space 2026 - Mad Rohim; Yanti Nuryanti; Eros Rosmina; Dewi Rahmawati; Feri Muhamad Firdaus; Ryan Hidayat (Journal of Language Development and Linguistics, 2026)
Language change within digital spaces has increasingly been observed on short video platforms such as TikTok. The use of Indonesian is no longer fully aligned with formal structures since it is shaped by fast paced and visually driven interaction. This study was conducted to examine how such transformation takes place through a pragmatic perspective. Data were obtained from TikTok content in 2026 including spoken expressions and supporting text. The analysis was carried out by tracing contextual meaning and communicative function in each interaction. The findings indicate that language forms tend to shift at the level of word choice and meaning delivery. Language use is also oriented toward expressing identity and creating social closeness. These results suggest that language transformation is not merely structural but also closely tied to the dynamics of digital communication.